2019
DOI: 10.1590/s0102-053620190108
|View full text |Cite
|
Sign up to set email alerts
|

Potential of aqueous extracts of basidiomycetes to control root-knot nematodes on lettuce

Abstract: The root-knot nematode (Meloidogyne incognita) is one of the main pests of lettuce due to the crop’s high susceptibility, unavailability of registered nematicides and lack of resistant cultivars. The aim of this study was to evaluate the potential of aqueous extracts of ten basidiomycete fungi for root-knot nematode control (in vitro and in vivo) on lettuce. The aqueous extracts of these fungi were initially evaluated in vitro in relation to their nematostatic and nematicidal activity. All extracts inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…for the control of root-knot nematodes (Aslam 2013; Okorie et al 2011). Aqueous extracts of 10 basidiomycetes were tested for M. incognita control; all extracts, particularly that of Pleurotus, inhibited hatching and increased J2 mortality (Wille et al 2019). Furthermore, the authors found that treatment of soil with fungal extracts reduced nematode reproduction by about 70%.…”
Section: Discussionmentioning
confidence: 99%
“…for the control of root-knot nematodes (Aslam 2013; Okorie et al 2011). Aqueous extracts of 10 basidiomycetes were tested for M. incognita control; all extracts, particularly that of Pleurotus, inhibited hatching and increased J2 mortality (Wille et al 2019). Furthermore, the authors found that treatment of soil with fungal extracts reduced nematode reproduction by about 70%.…”
Section: Discussionmentioning
confidence: 99%
“…High nematode mortalities (95%) were recorded for the acetonic and methanolic extracts, at 84% (v/v), respectively [23]. Finally, in a recent study, the aqueous extracts obtained from fruiting bodies of a number of EM, including Amanita muscaria, Boletus sp., Lactarius deliciosus, P. citrinopileatus, P. ostreatoroseus, P. ostreatus, P. pulmonarius, P. sajor-caju, Russula amethystina, and Suillus sp., were investigated to identify possible nematocidal activity against M. incognita [29]. After a 24 h in vitro confrontation, all mushroom extracts showed high nematocidal activities with mortality percentages reaching 90.7 to 100.0% [29].…”
Section: Activity Of Bioproducts From Edible Mushrooms Againstmentioning
confidence: 99%
“…However, to this date, there is no review article summarizing the body of research produced in the last four decades on the nematocidal effects of EM. The search for the potential use of the nematocidal compounds from different EM species has included a small number of studies using free-living nematodes [19][20][21][22][23][24][25] and some studies exploring the activity against parasitic nematodes of plants [17,20,22,[26][27][28][29] under in vitro conditions. More recently, different EM materials began to be screened for their nematocidal activity against larval stages of ruminant parasitic nematodes [8,[30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…However, antagonists and nematophagous microorganisms are the best potential substitutes for chemical nematicides. Few nematophagous bacteria and fungi are commercially available to control plant parasitic nematodes [19][20][21][22] . Among biocontrol agents fungi have complex strategies for capturing the nematodes by sticky branches, non-constricting and constricting rings, killing by producing toxic substances, and digesting by colonizing their reproductive structures [23][24][25] .…”
mentioning
confidence: 99%